The performance of Islamic banks during COVID-19 pandemic in Malaysia / Muhammad Akram Ramli - Ramli, Muhammad Akram (2021)
The purpose of this study is to identify which period that Islamic banks have better performance which from period of pandemic or no pandemic. The study also wanted to know is there any effect of government regulations like lower interest rate and moratorium which may effect to the banks performances. The dependent variable used to conduct this study is return on assets (ROA) while the independent variables used are size which is the log of company total assets, leverage which means total liabilities to total equity, profit margin where net profit to revenue and liquidity status which total liabilities to total assets. The panel data were used for the comparative between period that have pandemic and no pandemic based on 8 Islamic banks in Malaysia for second and third quarters 2019 and 2020 in determine the relationship between the dependent and independent variables in this study. The financial data were taken from banks annual report. Based on findings, all variables are shows significant results. Thus, it shows that these variables will represent the performance.